Extensively metastasizing leiomyosarcoma: A diagnostic challenge - Arvind Ahuja; Poojan Agarwal; Rohan Sardana; Suryanarayanan Bhaskar (Wolters Kluwer Medknow Publications, 2017)
Uterine leiomyosarcoma (ULMS) is a rare malignancy of the female genital tract and carries an extremely poor 5-year survival rate. It is known to metastasize early and to distant sites owing to a high propensity for hematogeneous spread. Lung, peritoneum, liver, and bone are relatively common sites of metastasis. Patient age, tumor size, FIGO stage, and grade of the tumor are important criteria for predicting metastasis. The incidence of ULMS is increasing, probably due to the use of improved imaging techniques and as a result of cancer patients' prolonged life expectancy. An early well thought diagnosis is only made possible if even in otherwise seemingly unsuspected cases, the histopathology slides are extensively screened and the treating clinician is alerted timely. We hereby report a case of an elderly female who underwent hysterectomy for resection of multiple fibroids in the uterus and later presented with distant metastasis to brain with the erosion of overlying skull bone, chest wall, and lungs. Microscopic features along with an extensive immunohistochemistry panel were used to ascertain tumor origin.